Human hybridomas constructed with antigen-specific Epstein-Barr virus-transformed cell lines. - Kozbor, D (1982)
A 6-thioguanine-resistant, human lymphoblastoid B-cell line (GM1500 6TG A-11; IgG secreting) was mutagen-treated with low-level gamma-irradiation and selected for ouabain resistance. One line showing 10,000-fold higher drug resistance, designated KR-4, was fused with an Epstein-Barr virus-transformed, cloned, B-lymphocyte cell line (B6) producing antitetanus toxoid (TT) antibody (IgM), and the hybrids were selected in hypoxanthine/aminopterin/thymidine medium containing 10 microM ouabain. Surviving cells, which arose at an optimal frequency of 10(-5), were subcloned by limiting dilution and screened for anti-TT production. Out of 395 final subclones, 372 were found positive for anti-TT, and seven that were selected for further study secreted specific antibody (IgM, kappa chain) at a maximum concentration of 3-6 micrograms/ml. The differential rate of anti-TT production during the logarithmic phase of cell growth was 15-fold higher in the hybridomas than in the original B6 line. The hybrid nature of the clones was confirmed by karyotype analysis, histocompatibility antigen typing, and expression of secreted and membrane-bound Ig classes. Biosynthetic labeling of the cells revealed that all hybrids secreted both IgM and IgG but that only the IgM class had specificity for TT. Because Epstein-Barr virus is a polyclonal B-lymphocyte activator, the technique we applied here may be useful for increasing the recovery of rare antigen-specific B cells in the peripheral blood and for improving the frequency and stability of hybridomas secreting a given antibody.